Implementation of the Role of Educators in Improving the Effectiveness of the Supervision of the Head of School in the World of Education - Ayu Kumala; Tobroni (Jurnal Pendidikan Nusantara, 2023)
Supervisors are made specifically and systematically in order to help stakeholders improve their daily tasks in the environment of the school institution, which is later expected so that teachers and supervisors can provide the best support for the learners who accumulate knowledge also to the guardians of the students who trust their children in the school. The study aims to find out why there are gaps in supervision that occur in the school environment in the conduct of its program of activities. This research uses a method of library study that is carried out using references from a variety of sources. The results of this study show that supervising can enhance the creativity and professionalism of teachers in teaching, but found shortcomings in the path of structural supervision and no horizontal guidance. This problem can be addressed by the way the head of school as a policymaker involves teachers in decision making so that the teacher concerned can provide input on actual events in the field that they experience every day.